RATIONALE FOR THE EFFECTIVE APPLICATION OF THE EXPERIENCE OF ANTI-TUBERCULOSIS CARE SETTINGS DURING THE COVID-19 PANDEMIC - O.I. BOBOKHOJAEV; S.D. PULATOVA; YU.YU. MIRZOALIEV (Avicenna Tajik State Medical University, 2024)
Objective: To summarize the experience of the anti-tuberculosis care (ATC) units of the Republic of Tajikistan (RT) to optimize medical aid to the population during potential outbreaks of respiratory infectious diseases. Methods: This study examines the experience and lessons learned after the COVID-19 pandemic in the RT, as well as the main provisions recommended for the partial reorganization of the ATC to ensure its readiness to function during outbreaks of respiratory infections. The standards and rules of antituberculosis infection control were used to develop preventive measures against the nosocomial spread of aerogenic infections in healthcare facilities and society. Results: The analysis revealed that maintaining of a sanitary and anti-epidemic regimen in healthcare institutions primarily involved a routine approach to the disinfection of medical facilities. However, in respiratory infections, adopting the experience of ATC RT was beneficial. It included strict adherence to infection control rules, social distancing, avoidance of crowded public places, restriction of unnecessary migration and public events, and the rigorous use of means of personal protection. The ATC also pioneered innovative approaches through various software, which have proven effective even under the restrictions imposed during the COVID-19 pandemic. Conclusion: ATC can serve as a coordinating link and an excellent example of how to prepare the healthcare system for various potential outbreaks of respiratory infections. It is necessary to integrate the ATC with other relevant institutions of the healthcare system, both functionally and structurally, to increase the effectiveness of preventive measures against the transmission of respiratory infections.